Making connections : Harnessing the diversity of strategy-as-practice research - Kohtamäki, Marko; Whittington, Richard; Vaara, Eero; Rabetino, Rodrigo (Wiley, 2022)
Strategy-as-practice (SAP) has become one of the most vibrant areas of contemporary strategy research in the past two decades. As the field has grown significantly, we have witnessed an emergence of distinct streams of research within the SAP research community. Thus, it is time to take stock of this body of work to better understand the structure of the field and provide a refreshed agenda for future research. Our review is based on bibliometric analysis and a systematic review of 340 articles. As a result, we identify the following six clusters of research: praxis, sensemaking, discourse, sociomateriality, institutional and process. Co-citation analysis shows significant disconnects between some of these clusters. Building on our review, we identify various ‘crossing strategies’ for connecting across four disconnects: (i) micro and macro; (ii) sociomaterial and discourse; (iii) critical and more mainstream; and (iv) practice and process perspectives. By harnessing diversity, these crossing strategies suggest rich agendas for future SAP research, ranging from digitalization to gender inequality.
Keywords: fi=Strateginen johtaminen|en=Strategic Management|